PENINGKATAN KOMPETENSI GURU KELAS SDN KOJADOI DALAM PROSES PEMBELAJARAN MELALUI SUPERVISI AKADEMIK SEMESTER II TAHUN PELAJARAN 2018/2019 - MUNIRA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The background of this School Action Research (PTS) is the low pedagogical competence of Class Teachers in the learning process in class. The solution is to streamline the implementation of academic supervision. The problem is whether the implementation of academic supervision can improve teacher pedagogical competence in the learning process in the first semester of 2018/2019 at SDN Kojadoi. The purpose of this study was to determine the effectiveness of the implementation of academic supervision in an effort to improve the pedagogical competence of Class Teachers in classroom learning, the benefit for school principals is to find out the improvement in teacher competency in the learning process. This research was carried out for two cycles, each cycle of activities four stages namely planning, implementing, observing, and reflecting. Indicators of success in this study are; 1) the results of the observation of the principal and observations of the teacher during the mentoring process have received an average score of> 4.0, 2) the final result> 85% of the total number of mentoring participants received an average score of> 70.00 (good category).The results of the study in the first cycle observation of the average School Principal (3.40), the observation of the average teacher (3.17) and the academic supervision results of the average grade teacher (68.56). In cycle II, the average school head observations (4.60) with the percentage of achievement (100%), the average teacher observation (4.50) with the percentage of achievement (100%) and the average academic supervision results (83.67) ) with a percentage of achievement (100%). Indicators of success have been achieved, the research was declared successful and terminated in the second cycle. Conclusions; The results of the research in the second cycle showed an increase in teacher competence in the learning process in the classroom. It is recommended that other school principals conduct similar research in an effort to improve teacher competency, and to similar class teachers to carry out the learning process in accordance with well-planned scenarios, responsibilities, and be serious in order to improve student learning achievement in accordance with the field of study / eye lessons that are his responsibility.